Annual Technical Meeting 1998
DOI: 10.2118/98-04
|View full text |Cite
|
Sign up to set email alerts
|

Improved Residual Light Oil Recovery By Air Injection (LTO Process)

Abstract: A new air injection technique, low temperature oxidation (LTO process), is described. Improved oil recovery from deep, light oil reservoirs is achieved by removing the ovgen in the injected air by spontaneous LTO reactions with the residual oil in the reservoir. The product of the LTO reactions is a 'yue gas", which displace the oil. Preliminary results of LTO reaction kinetics and oil recovery have been obtained using four North Sea light oils. The paper also contains some discussion of the safety issues rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…There is danger in the whole process in Air injection, every link must take safety measures, mainly to prevent the explosion problem in the process of air injection. Air process, Greeves [14,11], experimental study on the displacement, for the majority of light crude oil, low rate of injection air for oxygen consumption completely. Wisley basin oilfield is a fractured low permeability carbonate reservoir, which is one of the finest examples of air displacement project to be more successful, began in 1986, gas injection stops several times due to various reasons, during 1991-1993 annual outgassing of CO 2 , N 2 and hydrocarbon and gas tracer, showed that O 2 was completely consumed [15].…”
Section: Home and Abroad Air Injection Efficiency And Safety Facmentioning
confidence: 99%
“…There is danger in the whole process in Air injection, every link must take safety measures, mainly to prevent the explosion problem in the process of air injection. Air process, Greeves [14,11], experimental study on the displacement, for the majority of light crude oil, low rate of injection air for oxygen consumption completely. Wisley basin oilfield is a fractured low permeability carbonate reservoir, which is one of the finest examples of air displacement project to be more successful, began in 1986, gas injection stops several times due to various reasons, during 1991-1993 annual outgassing of CO 2 , N 2 and hydrocarbon and gas tracer, showed that O 2 was completely consumed [15].…”
Section: Home and Abroad Air Injection Efficiency And Safety Facmentioning
confidence: 99%
“…Other than the core flooding experiments, kinetic cell experiments, including accelerated rate calorimetry (ARC), differential scanning calorimetry (DSC), and small-batch reactor (SBR), have also been extensively applied to study the LTO exothermic activity, which all show that the LTO of a light oil has the ability to elevate the temperature. A different understanding on the LTO exothermicity causes researchers to consider the HPAI differently. Some researchers believe that the spontaneous ignition is the key to the HPAI and stated that the combustion propagation can produce extra oil from the oil reservoir after gas flooding. ,, However, other researchers ignore the thermal effect and state that the HPAI in a light oil reservoir can be viewed as a conventional flue gas flooding process, as long as oxygen in the injected air is removed efficiently by the LTO. , Furthermore, numerical simulation regarding the HPAI performance and how to overcome the oxygen breakthrough if oxygen was not consumed effectively were extensively studied by different researchers. The different understandings on the HPAI technique were mainly attributed to the lack of understanding on the LTO reactions. Because the controversy remains, more efforts need to be performed to better understand the mechanisms of the AIP under the LTO mode.…”
Section: Introductionmentioning
confidence: 99%